Respuestas

  • Usuario de Brainly
2013-12-10T22:37:34+01:00
Por definicion:

f ' (x) =lim    f(x+h) - f(x)
        h→0          h

Si f(x) = x²-16 , entonces:

* f(x+h) = (x+h)² - 16 = x²  + 2xh + h² -16
* f(x) = x²-16

Por lo tanto: f(x+h) - f(x) = (x² + 2xh + h² -16) - (x² -16) =  2xh + h²


Reemplazando en el limite:

f ' (x) = lim  (2xh +h²)  =  lim    2x + h    =  2x + 0 = 2x
        h→0          h          h→0


Por lo tanto: f ' (x) = 2x



Recta tangente para xo=4:


Lt :  y - f(xo) = f '(a)(x-a)

Por lo tanto:   Lt : y - (0²-16) = (2(4))(x-4)
                           y + 16 = 8x - 32
                             y = 8x - 48

Recta normal para xo =4

Ln : y - f(xo) =  - (x-xo)/(f '(xo))
      
Por lo tanto:  Ln :  y - (0² -16) = - (x-4)/(2(4))
                            y + 16 = - (x - 4)/8
                            y = -(x-4)/8  - 16